Longitudinal annular displacement by M‐mode (MAPSE and TAPSE) in twin‐to‐twin transfusion syndrome before and after laser surgery. (13th September 2015) - Ortiz, Javier U.; Crispi, Fatima; Yamamoto, Ryo; Masoller, Narcis; Cruz‐Lemini, Monica; Gómez, Olga; Bennasar, Mar; Lobmaier, Silvia M.; Eixarch, Elisenda; Martinez, Josep M.; Gratacós, Eduard
Abstract: Objective: To evaluate mitral and tricuspid annular plane systolic excursion (MAPSE and TAPSE) in fetuses with twin‐to‐twin transfusion syndrome (TTTS) before and after laser therapy. Methods: A prospective study in 24 fetal pairs with TTTS evaluated 24 h before and within 48 h after fetoscopy and 13 gestational age‐matched normal monochorionic fetal pairs. MAPSE and TAPSE were measured in an apical or basal four‐chamber view by placing the M‐mode cursor at the lateral valve ring. Results: Mean preoperative MAPSE (controls 3.6 ± 1.3 mm vs. donors 2.7 ± 0.8 mm vs. recipients 2.8 mm ± 0.9; P  < 0.001) and TAPSE (controls 4.4 ± 1.5 mm vs. donors 3.3 ± 1 mm vs. recipients 3.6  ± 1.1 mm; P  < 0.001) values were significantly reduced in both TTTS fetuses. When subdividing according to TTTS stages, changes were significant in both stage I–II and III–IV subgroups, although differences were more pronounced in the latter. All observations remained unchanged 48 h post‐fetoscopy. Conclusion: Both recipient and donor fetuses had decreased global longitudinal motion, even in early TTTS stages. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Twin‐to‐twin transfusion syndrome (TTTS) represents a severe hemodynamic disorder that mainly affects recipients in advanced Quintero stages. Mitral and tricuspid annular plane systolic excursion (MAPSE and TAPSE) are very sensitive markers of longitudinal myocardial motion, but have never been assessed in TTTS. What does this study add? This study evaluates for the first time MAPSE and TAPSE in TTTS fetuses. Both recipients and donors show decreased MAPSE and TAPSE values, even in early TTTS stages.